Intralesional Quadrivalent Human Papilloma Virus Vaccine Versus Candida Antigen in the Treatment of Multiple Recalcitrant Non-Genital Warts - Ibrahim Fouda; Hassan Abou Khodair Mohammed; Ghada Mohammed Yousef Mohammed (Mattioli1885, 2024)
Introduction: Warts are the most prevalent clinical manifestation of Human papillomavirus (HPV) infections, which vary in morphological pattern depending on the site of the body affected. Objective: To evaluate the safety and efficacy of intralesional quadrivalent HPV vaccine versus candida antigen in treatment of multiple recalcitrant non-genital warts. Materials and methods: A randomized- control clinical trial included 60 cases with multiple recalcitrant warts who were randomly distributed into three groups; Group I included 20 patients who received intralesional candida antigen at a dose of 0.3 mL of 1/1000 solution, Group II included 20 patients who received intralesional quadrivalent HPV vaccine at a dose of 0.3ml and Group III included 20 patients who received intralesional injection 0.3 ml of normal saline 0.9% as a control group). Each agent was injected at the base of the largest wart every three weeks until it was completely cleared, or for a total of four sessions. Results: the highest response rate was detected in the quadrivalent HPV vaccine group (75% complete response) followed by the candida vaccine group (40% complete response and 15% partial response). Also, regarding the distant response rate, the highest response rate was detected in the quadrivalent HPV vaccine group (72.7% complete response and 27.3 % partial response) followed by the candida vaccine group (33.3 % complete response and 50 % partial response). Conclusion: Intralesional immunotherapy appears to be effective and safe in treating multiple recalcitrant non-genital warts, with intralesional quadrivalent HPV vaccine outperforming intralesional candida antigen.